The Forecasting Residual Life of Corroding Pipeline based on Semi-Probabilistic Method - Noor, N.M; Yahaya, N.; Ozman, N.A.N; Othman, S.R (Universiti Malaysia Sarawak (UNIMAS), 2010)
This paper demonstrate calculation and prediction of pipeline residual life subjects to internal corrosion. The results shows the standard deviation of corrosion parameter affected the value of partial safety factor as corrosion progressing, hence amplify the conservatism of time to failure.